Membrane Processes for Industrial Wastewater Treatment – Demineralization Station - Hajduková, Jitka; Thomas, Jan; Malíková, Petra; Matúšková, Veronika (GeoScience Engineering, 2013)
The paper deals with treatment of wastewater produced by the energy industry using a membrane processes (electrodialysis). Prior to application of this technology, the influence of wastewater on the chosen type of membranes is solved. Specifically, it means eliminating the influence of formation soluble (insoluble) salts which could negatively affect water treatment by the chosen technology. The paper also summarizes the results of laboratory tests of electrodialysis with the aim to acquire treated wastewater of such quality meeting legislative limits for discharges to surface water (i.e. total dissolved solids below 1g.l-1).